2007
DOI: 10.1682/jrrd.2006.05.0052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of posttraumatic stress disorder and chronic severe pain in psychiatric outpatients

Abstract: Abstract-This cross-sectional study reports the prevalence and correlates of posttraumatic stress disorder (PTSD) and chronic severe pain in psychiatric outpatients (n = 295), a sample that has not previously been examined for the co-occurrence of these two disorders. Nearly half the participants (46%) met the Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition criteria for PTSD; 40% reported chronic severe pain; and 24% had both disorders. We compared four groups of subjects who had either bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 56 publications
3
60
1
1
Order By: Relevance
“…The high rate of comorbidity between chronic pain and PTSD has been well documented [5,9,[42][43][44], and results from this study are consistent with these prior epidemiologic studies that have identified high prevalence rates of chronic pain and PTSD. Previous literature has demonstrated associations between PTSD and intensified pain severity, disability, and interference [45][46][47]; however, at least one study did not corroborate this finding [4].…”
Section: Outcalt Et Al Veterans With Comorbid Chronic Pain and Ptsdsupporting
confidence: 89%
“…The high rate of comorbidity between chronic pain and PTSD has been well documented [5,9,[42][43][44], and results from this study are consistent with these prior epidemiologic studies that have identified high prevalence rates of chronic pain and PTSD. Previous literature has demonstrated associations between PTSD and intensified pain severity, disability, and interference [45][46][47]; however, at least one study did not corroborate this finding [4].…”
Section: Outcalt Et Al Veterans With Comorbid Chronic Pain and Ptsdsupporting
confidence: 89%
“…Previous research has found that individuals with PTSD and chronic pain report higher ratings of psychiatric distress, greater disability, and more intense pain compared with those with PTSD or chronic pain only. [27][28][29] These previous findings are in contrast to ours and suggest that the more substantial morbidity associated with comorbid PTSD and pain may happen specifically when pain is long-lasting or chronic. We did find that veterans with PTSD and at least one pain complaint were more likely to have experienced combat and to screen positive for depression, but these findings were not statistically significant, likely due to low power.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, increased clinical awareness and screening efforts are likely identifying PTSD symptoms among OIF/OEF veterans that might have gone undetected in veterans from previous conflicts. Studies have demonstrated both high levels of PTSD symptom severity among patients with chronic pain [54] and high rates of chronic pain among patients with PTSD [16][17]55]. PTSD symptom severity has been associated with poorer health functioning among OIF/OEF veterans [56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence exists within the scientific literature regarding the co-occurrence of and the relationship between PTSD and chronic pain [11][12][13][14][15][16][17][18]. Otis et al has published a comprehensive summary of theoretical models, including mutual maintenance and shared vulnerability, underlying comorbid chronic pain and PTSD [14].…”
Section: Introductionmentioning
confidence: 99%